2009
DOI: 10.1055/s-0029-1225352
|View full text |Cite
|
Sign up to set email alerts
|

Reconsideration of Insulin Signals Induced by Improved Laboratory Animal Diets, Japanese and American Diets, in IRS-2 Deficient Mice

Abstract: Current Japanese and American diets and Japanese diet immediately after the War were converted to laboratory animal diets. As a result, current laboratory animal diet (CA-1, CLEA) unexpectedly resembled the diet of Japanese after the War. This is considered to result in an under-evaluation of diabetes research using laboratory animals at present. Therefore, changes in insulin signals caused by current Japanese and American diets were examined using IRS-2 deficient mice ( IRS2(-/-) mice) and mechanisms of aggra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…deficient mouse given a high fat diet developed impaired glucose tolerance from insulin resistance dependent on the fat content of the diet [14]. Because the hyperinsulinemia occurred in the SPF group and the insulin concentration in the GF group was basically the same as that in the Conv group, the impaired glucose tolerance found in the GF and SPF groups was not considered to be caused by an insulin secretory defect but by an increase in blood glucose concentrations due to strong insulin resistance.…”
Section: Discussionmentioning
confidence: 97%
“…deficient mouse given a high fat diet developed impaired glucose tolerance from insulin resistance dependent on the fat content of the diet [14]. Because the hyperinsulinemia occurred in the SPF group and the insulin concentration in the GF group was basically the same as that in the Conv group, the impaired glucose tolerance found in the GF and SPF groups was not considered to be caused by an insulin secretory defect but by an increase in blood glucose concentrations due to strong insulin resistance.…”
Section: Discussionmentioning
confidence: 97%
“…Data for the B6J-Irs2 -/-mouse are presented in this paper. The descriptions and data in the following sections are cited and abstracted from previous publications [2,[7][8][9][10].…”
Section: Irs2mentioning
confidence: 99%
“…When research on the ontogenetic characteristics of B6J-Irs2 -/-mice began, Kagohashi et al of Shimane Univer-sity reported that onset of type 1 diabetes in NOD mice produced by embryo transplants into ICR or DBA/2J recipients was later than that in NOD mice reared by foster mothers [17]. The B6J-Irs2 -/-mice used in the investigation of ontogenetic characteristics [7] were prepared by in vitro fertilization and embryo transfer. -/-(D1-3) mice sera reacted with pancreatic sections.…”
Section: Comparison Of B6j-irs2 -/-Mice Mated Naturally or Produced Bmentioning
confidence: 99%
“…Effects of modern Japanese and American diets on RNA expression of GLUT4 and PPAR 2 of adipose tissues and plasma adipocytokines concentrations in IRS-2 deficient mice fed with three kinds of diets with different lipid levels. regular and Japanese and American diets as well as tap water ad libitum for 2 weeks, and used for glucose tolerance test, insulin tolerance test, and harvests of blood, liver, femoral muscles, white adipose tissue (WAT), and pancreas for chemical analysis at the age of 6 weeks (Hashimoto et al, 2009). Average body weight of Rd, Jd and Ad group at 6 week of age were 20.8, 22.7 and 22.9g each.…”
Section: Metabolic Characteristics In Irs-2 Deficient Micementioning
confidence: 99%